Saunders equine formulary - Knottenbelt, Derek C. (Saunders, 2015)
This new edition is the only equine formulary available both in print and as an app for mobile use. Written by a world-renowned expert on equine medicine, Derek Knottenbelt, this book is an indispensable reference for equine veterinary practitioners, veterinary students, and others involved in breeding and keeping horses